Presencia de pycnodontiformes en el cretáceo inferior de colombia (1970)
It is the first time that the existence of a Pycnodontidae which can be approximately attributed to Macromesodon Couloni (Agassiz) is described in Colombia. The age would correspond to the Barremian-Aptian.